Considerations for state-imposed conditions on healthcare provider transactions - Montague, Alexandra D.; Davison, Robin L.; Gudiksen, Katherine L.; King, Jaime S. (Frontiers in Public Health, 2023)
The widespread consolidation of health systems, hospitals, and physicians has contributed to the high price of healthcare across the United States. While federal antitrust enforcers continue to play an important role in overseeing large mergers, acquisitions, and other consolidating transactions of major healthcare providers, state oversight over healthcare markets is essential to slow consolidation more broadly and address market failures across the country. State laws govern the scope of authority held by state attorneys general and other state agencies to receive notice of, review, and approve, conditionally approve, or block healthcare provider transactions, which can significantly impact the breadth and content of oversight. While blocking potentially anticompetitive transactions can help states maintain any competitive forces that remain in the market, in some situations, approving a transaction with conditions may be the best path forward. Applying conditions to transactions may allow state officials to oversee and govern the behavior of providers post-transaction while states pursue other legislative fixes. Although the use of conditions is a relatively common practice at the state level, little research has been done to explore their use among states. Following a search in all 50 states, this paper examines decisions from state officials imposing conditions intended to address the impacts of transactions on healthcare price, access, and quality and provides recommendations for the effective use of conditions moving forward.